Kaupod The life and works of Joel Arbolario (1952-2003) - Nava, Ma. Cecilia Locsin (Saliksik kultura: the NCCA Research Journal, 2021)
The research is an attempt to shine a light on a vernacular playwright whose incontrovertible contribution to Negrense theater is enormous but who is not particularly known nationally. By analyzing his works and translating one of them, the researcher hopes to establish Joel S. Arbolario’s position in Philippine theater especially in relation to his instituting a nationalist theater in Bacolod City called Kalingaw: Ang Teatro Hiligaynon. In the process, the researcher hopes to contribute to the national effort to help write a holistic history of Philippine literature as envisioned by National Artists Bienvenido Lumbera and Resil Mojares in the 70s and level the playing field for regional writers who, because they are at the periphery of culture, power and civilization, are given scant attention since they are considered “minor” – not, in Homi Bhabha’s words, “out of a question of essence…but [out of] subject position”.